Nauka podczas wojny. Praktyki edukacyjne i szkolnictwo w dobie konfliktu w Ukrainie - Drozdowicz, Jarema (Humaniora. Czasopismo Internetowe, 2024)
The paper attempts to highlight key aspects of the impact of war in Ukraine on educational practices ans schooling system not just in the Ukraine alone, but also in a broader context of the collective West. The role of the school becoes thus crucial in understanding how war influcences the changes in the public sphere, but also influences directly practices and coping strategies allowing educators and academics to continue with their work. The effect of war on ukrainian pupils and chidlren is yet to be edtimated, however it becoes clear now that the long term conseqences of the Russian agression will force educators to introduce new pefdagogical tools and methods in order to deal with the psychological trauma and learning deficits related to war time operations. The issue of war education affects not only schools but also universities. The case of the Pedagogical University of Bierdyansk might serve here as an example how bottom up direct actions and cooperation between students, academics, and local authorities helps to maintain the learning and scientific activity despite obvious obstacles. The text identifies therefore main boundaries and issues of war education with the goal of redefining educatioanl paradigms and adjusting them to the contemporary context.